Augmented Reality dalam Pembelajaran Geometri: Dampak, Tantangan, dan Arah Masa Depan - Asmaun Asmaun (PT. Lontara Digitech Indonesia, 2025)
The development of digital technology in education has opened new opportunities for innovation in mathematics learning, particularly in geometry, which demands high spatial visualization skills. One rapidly developing innovation is Augmented Reality (AR), a technology that interactively combines real-world and virtual elements. This article is a systematic literature review that aims to examine the trends, effectiveness, and challenges of AR integration in geometry learning. Data were obtained from articles indexed in Scopus, Sinta, and Google Scholar, which were then analyzed thematically based on the research focus, empirical results, and their contribution to mathematics learning. The results of the study indicate that the application of AR can improve spatial ability, conceptual understanding, as well as student engagement and motivation in learning. Applications such as GeoGebra AR and 3D AR Escape Room have proven effective in supporting the visualization of geometric concepts and connecting theory to real-world contexts. However, the success of AR implementation is still influenced by factors such as device availability, teacher digital literacy, and pedagogical design that are not yet fully integrated. This study recommends the development of more adaptive and contextual AR-based learning models, as well as further research regarding the long-term impact of AR on higher-order geometric thinking skills.